Effects of Radiation sterilization Dose on the Molecular Weight and Gelling Properties of Commercial Alginate Samples - Mollah, M. Z. I.; Rahaman, M S.; Faruque, M R I.; Khandaker, M U.; Osman, Hamid; Alamri, Sultan; Al-Assaf, Saphwan (Frontiers in Materials, 2021)
A total 26 alginate samples; control (13) and 15 kGy γ-irradiated (13) were characterized by viscometric and GPC-MALLS methods for the molecular weight (Mw). Remarkable decreasing changes in intrinsic viscosity for all samples of alginates were observed by the effect of radiation with a linear relationship between viscosity and concentration in 0.01 M NaCl solution. The results of molecular weight (Mw), % mass recovery, radii of gyration (Rz/Rg), % reduction of molecular weight assessed by gel permeation chromatography (GPC) and found significant correlation. The molecular weight decreased dramatically by the effect of radiation with momentous relation to the % reduction of the molecular weight. The highest molecular weight reduction (84%), which is the most sensitive to γ-radiation, average reduction rate was ≥50%. Thus, the samples were to be sensitive by 15 kGy radiation for Mw distribution.